Comparative Analysis Of Implementation Plan Costs Between Daily Wages And Contract Wages In Building Construction Projects (Case Study Of Jakarta Islamic Hospital Pondok Kopi) - Dwi Novitasari; Nikko Rozy (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
In this study, researchers reworked the RAB (Budget Plan) that was not previously obtained from the research site. The expected outcome of processing the RAB data is to identify which jobs have the greatest weight and require piecework wages. This is then compared to the RAP. Because of this simple point, errors still occur frequently in some projects, resulting in budget overruns. This daily and piecework wage system often occurs in projects. Therefore, the author wants to conduct an analysis of the comparative cost of the Jakarta Islamic Hospital Development Project Pondok Kopi, between the work analysis according to the Cost Budget Plan based on the results of the survey based on daily wages and the Cost Budget Plan based on the results of the survey based on piecework wages based on the Cost Budget Plan. Differences in wage systems significantly impact project cost efficiency. Daily wages tend to provide workers with income security, but they risk reducing productivity if there is no close supervision. Conversely, piecework wages can increase productivity due to the incentive to complete work more quickly, but they can potentially reduce quality if supervision is suboptimal. This research is relevant to the Jakarta Pondok Kopi project, where challenges such as tropical weather and material availability require an adaptive wage approach.